PENDAPINGAN PARA LANSIA DALAM PELESTARIAN SEKAR MADYA KEKIDUNGAN PENETRALISIR AURA-AURA NEGATIF SEBAGAI TRADISI LELUHUR DI DESA TUMBAKBAYUH, KECAMATAN MENGWI, KABUPATEN BADUNG, PROPINSI BALI (Perspektif, Bentuk, fungsi Kidung Bhuta Yadnya) - I Ketut Muada; I Wayan Sugama; I Made Indra Sanjaya (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Tembang has an important role in the life of the Hindu community in Bali. Learning tembang will also teach you language, script, meter, cultural concepts and the values ​​contained in this literature. Tembang means nembang which is associated with the word kembang meaning flower. Flowers or sekar have a role and function as a source of beauty where the God Kama (God of beauty) resides. In reality, as a generator of lust, it is in line with the role and function of flowers or Dewa Kama during ceremonies in Bali. The role of elderly fathers and mothers today in pursuing songs in Bali is a huge appreciation for the entire Balinese people. In preserving Balinese songs, these elderly people never stop learning so that they are useful for the lives of today's society, especially since Covid-19 has passed and is a warning for all of us to always be alert. For the elderly in Tumbabakbayuh Village, Mengwi District, Badung Regency, this is motivation to learn to find a solution so that these things do not happen again. Preserving the vocals of the song kekidungan bhuta yadnya is a method of learning ancestral heritage that is effective in warding off the negative auras that exist on this earth